Combining Ability of Some Agronomic Characters of Sweetwaxy Double Recessive Maize Inbred Lines (Bangladesh Journal of Botany, 2023)
The present study was undertaken to explore more excellent sweet-waxy maize germplasm resources and provide a theoretical basis for the rational application of sweet-waxy maize inbred lines. Eight sweetwaxy maize inbred lines VB. RN1621, RN1423, RN1432, RN1636, RN1441, RN1443, RN1457 and RN1669 were selected as female parents (P1) and three sweet-waxy maize inbred lines e. g. LN505, LN506 and LN515 were taken as male parents (P2). Using incomplete diallel cross NCII design, 24 combinations were configured to analyze the combining ability of eight agronomic characters such as plant height, ear height, ear grain weight, ear length, number of grains per row, hundred-grain weight, peel residue rate and amylopectin content. It was obaerved that the order of general combining ability was RN1669, RN1636 and LN506. The combination with the highest effective value of special combining ability was RN1641 × LN506, RN1621 × LN506 followed by RN1657 × LN506 which ranked third. Plant height, panicle grain weight and bark residue rate should be selected in the early generation. The ear height, ear length, 100-grain weight and amylopectin content may be selected in the late generation, which can be used for sweet-waxy maize breeding.Bangladesh J. Bot. 51(4): 849-854, 2022 (December) Special